Estudio técnico financiero de la instalación de una planta de licuefacción de gas natural a pequeña escala para uso de éste como combustible en el sector transporte automotor en Colombia (2018)
The project analyzed a supply and demand study of natural gas and diesel in heavy transport in Colombia, to evaluate the main strategic points where natural gas liquefaction plants could be located to provide LNG supply to gas stations. fuel service. Then a technical study of some of the designs of the equipment that Peru and Spain has for the operation of the liquefaction plant on a small scale was carried out, giving as the best design a SMR plant, which used the information for the realization of a design in the Aspen Hysys simulation software, which favors the process of liquefaction, transport, storage and distribution on the routes, Bogotá - Medellín - Cartagena, Bogotá - Barrancabermeja - Cartagena and Bogotá - Buenaventura. In the analysis of supply and demand of natural gas and diesel in the automotive transport sector, resulted in greater demand in the plant Tuluá-Andalucía and lower demand in the plant located in Bello-Antioquia. Feasibility was evaluated with the technical and a financial study of the general investment needed for the installation of a small-scale natural gas liquefaction plant in Colombia and its economic sustainability with the natural gas to be liquefied to sell to the gas stations. service that could have LNG and that could or currently have NGV as fuel for the transport sector.